Proceedings of the 16th International Conference on World Wide Web 2007
DOI: 10.1145/1242572.1242602
|View full text |Cite
|
Sign up to set email alerts
|

The complex dynamics of collaborative tagging

Abstract: The debate within the Web community over the optimal means by which to organize information often pits formalized classifications against distributed collaborative tagging systems. A number of questions remain unanswered, however, regarding the nature of collaborative tagging systems including whether coherent categorization schemes can emerge from unsupervised tagging by users. This paper uses data from tagged sites on the social bookmarking site del.icio.us to examine the dynamics of collaborative tagging sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
381
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 483 publications
(397 citation statements)
references
References 11 publications
13
381
0
3
Order By: Relevance
“…Formal folksonomy models are e.g. presented in [7,8]. They are based on bindings between users, tags, and resources.…”
Section: Faceted Taggingmentioning
confidence: 99%
“…Formal folksonomy models are e.g. presented in [7,8]. They are based on bindings between users, tags, and resources.…”
Section: Faceted Taggingmentioning
confidence: 99%
“…Different studies showed already that it is possible to learn hierarchical relations among tags by exploiting traditional folksonomy structures. For example, Halpin et al extract sub-class relations by exploiting correlations between tags induced by co-occurrence of tags [14] and Mika mines narrower and broader concepts by detecting communities and sub-communities within the tripartite graph spanned by traditional folksonomies [15] (cf. weighted tripartite graph in Section 3.1).…”
Section: Learning Tag Relationsmentioning
confidence: 99%
“…The work by Mika [17] considers a tri-partite model of instances, users, and concepts and mines the relationships among these three entities. [8,16,7] have concentrated on understanding the tagging process and the resulting social annotations by examining tag distributions, constructing tag-tag correlation networks and extracting statistics of users' tagging behavior. [14] investigate the overlap between anchortext and tags for a Web page.…”
Section: Related Workmentioning
confidence: 99%